Challenges and Hurdles Regarding Free and Fair Elections in India: A Study of Voters' Opinion - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana (Integrated Journal for Research in Arts and Humanities, 2022)
India claims to be the world's largest democracy. Over the last 65 years, it has seen the execution of successful electrical campaigns, peaceful changes in the government at Focus and in the States, and people guiding freedom of speech and articulation, religion, and progress. India is experiencing social and economic change. Similarly, we constantly consider arguments about the prevalent inequities, lack of assumed fulfillment, and betrayal of some elements of society. Individuals do not feel like they are participating in this complete voting procedure. This is because a system based on majority rule represents the public authority of the people, for the people, and by the people. It implies that a majority-rules government is not confined to the system of choices but also to fulfilling people's economic and social desires. People in our country discuss different aspects of a majority rule system, including its successes and drawbacks. In this method, a large number of investigations have been conducted.